Hydroelectric power station : Nigerleq - Lauritsen, Mads Uhrenholt 1989- (2016)
This report contains a pre-feasibility study and an evaluation of a potential new 3 MW hydroelectric power station utilizing two separate reservoirs located in the Nigerleq area in close proximity to the city of Paamiut in Western Greenland. This purpose of this research is to determine if the project promises enough value to proceed to the next stage of development. The Nigerleq area has previously been investigated and found financially unviable, but with rising diesel cost, increased focus on sustainability and new flow and discharge measurements available, Nukissiorfiit1 wishes the project re-evaluated. The site has been surveyed and a first-estimation of power plant design is proposed in this report. Along with the technical aspects of the project, a financial evaluation based on a cost-estimation of the project is presented, proving that the Nigerleq hydropower station could provide a valuable addition to the energy system in Paamiut and Greenland. Measurements show that the Nigerleq low reservoir has an average discharge of 0.94m3/s and a headnet height of 147m, while the Nigerleq High reservoir provides an estimated discharge of 0.39m3/s and a headnet height of 393m. This report proposes to install a combined capacity of 3MW spread between two horizontal twin-jet Pelton turbines to allow for optimal generation strategy, providing approximately 19.8 GWh annually. The Nigerleq Low reservoir is connected to the powerhouse via a 1100m long transport tunnel and a 1130m long DN900 steel penstock leading the flow to the 1.4MW turbine, driving a 12 pole synchronous generator. The Nigerleq High reservoir connects to the powerhouse via a 2500m long DN600 steel penstock leading the flow to the 1.6MW turbine, driving a 4 pole synchronous generator. Estimated budget of the hydroelectric power station is 155.000.000 DKK with construction being finished in year 2020. The financial analysis, based on a discount rate of 4% and an investigated period of 50 years, proves a positive national and corporate value of the ...